Voicing Women’s Underrepresentation in Speeches: A Framing Analysis - Rofiq, Zainur (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
Despite decades of gender equality advocacy, women still face significant barriers that limit their access to influential platforms and their impact once on these platforms. Analyzing how women's speeches are framed provides valuable insight into the dynamics of their underrepresentation, helping us uncover the structural and cultural constraints that shape societal perceptions of women leaders. This paper explores how women leaders and activists frame issues of gender inequality, human rights, and women's empowerment in the various spheres of political discourses. Using five speeches of influential women (i.e., Hillary Clinton, Kamala Harris, Angela Merkel, Malala Yousafzai, and Aung San Suu Kyi) as data, this study analyzes how framing constructs public perceptions of gender roles and influences the attitudes of society. Framing concepts coupled with rhetorical strategies by leaders can define problems, attribute the cause(s), construct moral imperatives, and put forth solutions to the systemic set of gender disparities. This analysis underlines framing as a tool that not only has symbolic and transformative power, but can also reshape the perception of women in leadership and stimulate political participation to enable societal change. Understanding these dynamics is of significance for greater inclusiveness in fostering the aspirational value of the global issue of gender inequalities.